Persetujuan Tindakan Kedokteran Sebagai Bagian Perjanjian Terapeutik di Puskesmas Desa Sungai Jambat - Sarina Lestari, Besse; Budhiartie, Arrie; Alissa, Evalina (Universitas Jambi, Fakultas Hukum, 2024)
The aims of this research are to find out and analyze whether (1) What are the elements of informed consent that are implemented at the Sungai Jambat Village Health Center. (2) What are the exceptions to the absence of informed consent in a therapeutic agreement at the Sungai Jambat Village Health Center. The methodology had been used was an empirical juridical legal research regarding the application or implementation of legal provisions directly to every legal event that occurs in society. The results of this research indicate that the implementation of informed consent at the Sungai Jambat Village Health Center has been legally enforced as law because it implements and fulfills the four elements of the agreement in Article 1320 of the Civil Code, agreed after receiving the information, competent because they are 21 years old. and guardianship if under age, a certain thing related with the medical action/treatment, and the object of the agreement is fulfilled, and the last requirement related with the legally reason has been eligible because the object of the agreement were the medical treatment that accordance and do not deviate from the law. Regarding the exception to the absence of informed consent, the Sungai Jambat Village Health Center stipulates the rule that in an emergency situation, as an effort to save the patient and requires immediate action, informed consent is not required and can be requested after medical action has been given.